Pengaruh Harga Produk dan Kelengkapan Produk Terhadap Keputusan Pembelian Konsumen - Surya Dhama, Tedyanto; Suratno, Eddy; Paul Karolus Pasaribu, Johni; Alberta Ingriana (Journal of Trends Economics and Accounting Research, 2024)
The purpose of this study was to determine the effect of price and product completeness on consumer purchasing decisions at CV. Karya Inti Makmur. There are so many factors that can influence consumer purchasing decisions which are internal and external factors. However, the most prominent among these factors are price and product completeness.This research is quantitative research whose research results are the accumulation of data from a number of respondents who are consumers of CV. Karya Inti Makmur. This research test uses linear regression tests. In this study there are independent variables and dependent variables. The dependent variable consists of purchasing decisions (Y) while the independent variable consists of price (X1) and product completeness (X2). This study has 96 respondents who have data to test.The results of his research are that there is an influence between price on consumer purchasing decisions partially and an influence between product completeness on consumer purchasing decisions partially. The effect of price and product completeness variables on purchasing decisions is 61.9% and the rest of consumer purchasing decisions are influenced by other variables besides price and product completeness.